to chromosome level - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Cytogenetics of the genus Musa By K Sheperd, INIBAP, 1999. 160 pp. ISBN 2 910810 25 9 Freely available for download as PDF file at: www.inibap.org/publications/monographs/monographs_eng.htm